Retracted: C4d deposition in native kidney disease and its correlation with proteinuria and serum urea/creatinine - Pandey, Sant; Yadav, Sucheta; Babu, Suresh; Kumar, Ashutosh; Singh, Bhupendra P.; Wakhlu, Anupam; Singhai, Atin; Sonkar, S. K.; Pooniya, Vishal (International Journal of Research in Medical Sciences, 2018)
The article titled, "C4d deposition in native kidney disease and its correlation with proteinuria and serum urea/creatinine", published in the International Journal of Research in Medical Sciences, Volume 6, Issue 12, 2018, Pages 3935-3941, DOI: http://dx.doi.org/10.18203/2320-6012.ijrms20184886 is being retracted. We received complaint from one of the co-authors, after publication of the article that corresponding author, Dr. Sant Pandey had submitted the manuscript without informing other co-authors and it was not his original work. We contacted the corresponding author who could not satisfactorily respond to our queries. Since the author could not satisfactorily defend his paper and contravened the declaration he made while submitting his manuscript, it was decided to retract the article from International Journal of Research in Medical Sciences and not to consider any manuscript submitted by him in future.